2021
DOI: 10.1186/s12885-021-08347-w
|View full text |Cite
|
Sign up to set email alerts
|

Extending screening intervals for women at low risk of breast cancer: do they find it acceptable?

Abstract: Background Trials of risk estimation in breast cancer screening programmes, in order to identify women at higher risk and offer extra screening/preventive measures, are ongoing. It may also be feasible to introduce less frequent screening for women at low-risk of breast cancer. This study aimed to establish views of women at low-risk of breast cancer regarding the acceptability of extending breast screening intervals for low-risk women beyond 3 y. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(131 citation statements)
references
References 34 publications
6
125
0
Order By: Relevance
“…This is consistent with UK surveys demonstrating that between 53% and 58.5% of women would consider a screening interval of 4–5 years if they were assessed as low-risk [ 14 , 20 ]. Our findings also correspond to McWilliams et al, who found the acceptability of less frequent screening at low-risk to be contingent to perceived accuracy of PRA and evidence-based low-risk screening recommendations [ 26 ]. Although ’overall acceptors’ had mixed responses to foregoing screening if assessed as very low-risk, some thought this option would be acceptable with individual guidance concerning the balance of screening benefits and harms and/or were able to perceive this as more acceptable for younger women un-endowed with NHSBSP experience.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is consistent with UK surveys demonstrating that between 53% and 58.5% of women would consider a screening interval of 4–5 years if they were assessed as low-risk [ 14 , 20 ]. Our findings also correspond to McWilliams et al, who found the acceptability of less frequent screening at low-risk to be contingent to perceived accuracy of PRA and evidence-based low-risk screening recommendations [ 26 ]. Although ’overall acceptors’ had mixed responses to foregoing screening if assessed as very low-risk, some thought this option would be acceptable with individual guidance concerning the balance of screening benefits and harms and/or were able to perceive this as more acceptable for younger women un-endowed with NHSBSP experience.…”
Section: Discussionsupporting
confidence: 88%
“…This work introduced women to PRA and RSBS and explored their thoughts and feelings about the prospect of incorporating this approach within the NHSBSP. To date, there has only been one qualitative interview study assessing the acceptability of this novel screening approach amongst UK women [ 26 ]. As McWilliams and colleagues aimed to explore women’s perceptions of extended screening intervals having been identified as low-risk through their participation with the BC-Predict study [ 27 ], this is the first study to provide a more comprehensive overview of how women think and feel about the prospect RSBS as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such concerns around accepting reduced screening for those at low risk have been reported previously. 13,14,28,[30][31][32]35 Coupled with findings that overdetection in population screening is acceptable to the public and that many are willing to undergo diagnostic testing regardless of cancer risk, 36,37 this reinforces the relatively low importance placed by the public on the potential harms of screening people at low risk.…”
Section: Comparison With Existing Literaturementioning
confidence: 88%